Lead-212 Radiopharmaceuticals for Receptor-Targeted Radionuclide Therapy - Solmaz Mojarad-Jabali; Sajjad Molavipordanjani (Journal of Mazandaran University of Medical Sciences)
Receptor-targeted radionuclide therapy (RTRT) combines the power of particle-emitting radionuclides with the receptor-targeting capabilities of biomolecules, including antibodies and peptides. There are numerous radionuclides, but only a handful possess the necessary characteristics for targeted alpha therapy (TAT). Among them are actinium-225 (²²⁵Ac), bismuth-213 (²¹³Bi), radium-224 (²²⁴Ra), lead-212 (²¹²Pb), thorium-227 (²²⁷Th), astatine-211 (²¹¹At), and terbium-149 (¹⁴⁹Tb). Lead-212 (²¹²Pb) is a radionuclide that release both alpha and beta particles during its decay. The distinctive properties of ²¹²Pb, such as its relatively short half-life (10.64 hours), the commercial availability of ²²⁴Ra/²¹²Pb generators, in vivo generation of alpha particles through ²¹²Bi at its target site, simple conjugating process, and strong binding to chelators such as DOTA and TCMC make this radionuclide particularly promising for targeted alpha therapy. TAT with ²¹²Pb has demonstrated significant therapeutic effectiveness in both in vitro and in vivo models. To date, numerous biological molecules, including antibodies and peptides, have been labeled with ²¹²Pb in preclinical studies to evaluate their therapeutic efficacy and receptor-targeting potential. These studies have focused on receptors such as the epidermal growth factor receptor (EGFR) family, somatostatin receptor 2 (SSTR2), melanocortin 1 receptor (MC1R), prostate-specific membrane antigen (PSMA), CD37, CD38, CD46, vascular cell adhesion molecule 1 (VCAM-1), and chondroitin sulfate proteoglycan 4 (CSPG4). This review will first examine the physical properties of ²¹²Pb, followed by an analysis of its chemical characteristics, particularly its interactions with DOTA and TCMC. Finally, it will explore preclinical studies on ²¹²Pb-radiolabeled molecules and assess the clinical applications of radiotracers developed for receptor-targeted radionuclide therapy.